Longitudinal changes in athletic performance in competitive figure skaters - Cruz, J. P.; Vriner, M.; Mangum, L. C.; Slater, L. (Journal of Science in Sport and Exercise, 2021)
Purpose: To measure changes in strength, power, and agility over consecutive seasons based on competition level in figure skaters. Methods: A total of 197 competitive singles figure skaters (age range = 9-25 years old) completed combines with United States Figure Skating on two consecutive seasons between 2011 and 2018. Skaters either remained in the same competitive on-ice level or increased by one level on consecutive seasons. All athletes completed the hexagon agility test, maximal vertical jump, timed tuck jumps, push-ups, and bent knee v-ups. Repeated-measures analyses of variance separated by sex with Tukey`s post hoc were performed for each dependent variable and Cohen`s d effect sizes were calculated for all significant differences. Results: Female skaters who remained in the same level demonstrated improved performance on vertical jump (3.66 cm higher), timed tuck jumps (3.77 more jumps), v-ups (1.59 more v-ups), and hexagon jump (1.17 s faster). There was an interaction for female skaters who remained in the same level (P = 0.004), with senior and junior levels outperforming intermediate level skaters on the hexagon jump test. Female skaters who increased level demonstrated improved performance on the vertical jump (2.24 cm higher), hexagon jump (1.16 cm faster), and tuck jump (3.03 more jumps). Male skaters did not demonstrate any changes in performance except v-ups (2.86 more v-ups) for those who increased level. Conclusions: The greatest changes were in lower level female skaters who remained in the same level, supporting the importance of participating in strength and conditioning programs earlier in skating careers to maximize athleticism before reaching the senior level, when changes in off-ice performance plateau.